PENGARUH SOCIAL COMPARISON TERHADAP BODY DISSATISFACTION PADA PEREMPUAN DEWASA AWAL PENGGUNA INSTAGRAM DI KOTA MEDAN - Putri Rohni Agustina Haloho; Nenny Ika Putri Simarmata (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of social media, particularly Instagram, has increased individuals' tendency to engage in appearance-based social comparison. Continuous exposure to idealized body images on Instagram may contribute to body dissatisfaction, especially among young adult women who are at a developmental stage characterized by heightened concern about physical appearance. This study aims to examine the effect of social comparison on body dissatisfaction among young adult female Instagram users in Medan City. This research employs a quantitative approach using a simple linear regression analysis. The study population consists of young adult female Instagram users residing in Medan City. The sample is selected using a non-probability sampling technique through a combination of purposive sampling and convenience sampling based on predetermined inclusion criteria. Data are collected using a Social Comparison Scale developed based on the theory proposed by Schaefer and Thompson (2014) and a Body Dissatisfaction Scale adapted from the concept developed by Cash and Pruzinsky (2002). The collected data are analyzed using descriptive statistics, assumption tests, and simple linear regression analysis to examine the influence of the independent variable on the dependent variable. The proposed hypothesis states that higher levels of social comparison are associated with higher levels of body dissatisfaction among young adult female Instagram users in Medan City. The findings of this study are expected to contribute to the development of psychological science, particularly in understanding the impact of social media use on women's body image, and to provide a reference for developing preventive interventions aimed at promoting positive body image and mental well-being among social media users.